2020
DOI: 10.26858/eralingua.v4i1.11001
|View full text |Cite
|
Sign up to set email alerts
|

Edmodo-Based Learning and the Students’ Perception

Abstract: In the 4.0 era, technology is taking a part of many fields, including education. This research aimed is to find out about the perception of students about English class based on online method using Edmodo as medium. Descriptive qualitative method is used in this research. The respondents are the students who took English class and came from different department. This shows that the students preferred online method by using Edmodo for English Class. However, there is still drawbacks of using it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This result is consistent with the previous studies that referred to the effectiveness of hybrid learning in developing higher cognitive abilities and skills of the students. for example, the studies of (Sriarunrasmee, et, al.,2015, andWahyuni et al, 2019) indicated that the integration of synchronous and e-learning encourages students to improve their logical reasoning abilities and the findings of (Tamrin & Basri, 2020) that clarifies that when students can use the lecturer's resources to learn anywhere, at any time, and either cooperatively or individually this can empower their cognitive and thinking abilities.…”
Section: Resultsmentioning
confidence: 94%
“…This result is consistent with the previous studies that referred to the effectiveness of hybrid learning in developing higher cognitive abilities and skills of the students. for example, the studies of (Sriarunrasmee, et, al.,2015, andWahyuni et al, 2019) indicated that the integration of synchronous and e-learning encourages students to improve their logical reasoning abilities and the findings of (Tamrin & Basri, 2020) that clarifies that when students can use the lecturer's resources to learn anywhere, at any time, and either cooperatively or individually this can empower their cognitive and thinking abilities.…”
Section: Resultsmentioning
confidence: 94%
“…The results showed that there are no statistically significant differences between the mean scores of the teachers between the two experimental groups. The researchers clarify that this is due to the importance of these two learning environments and that they focus on different aspects of the learners, and neither of them replaces the other, and this is supported by the results of several studies that dealt with the feasibility and usefulness of social e-learning environments as the study of (Altunkaya and Ayrancı, 2020), and (Tamrin and Basri, 2020) study on developing cognitive and performance skills, as well as what was indicated by the study of (El-feky, 2019) which emphasized the role of the personal learning environment on developing those skills. With this result, this study highlights the appropriate use of social and personal E-learning environments in the training Table 9.…”
Section: Recommendationsmentioning
confidence: 96%
“…The use of technology in learning can help students be more creative and efficient in an interactive learning environment. Students can explore knowledge from various types of learning resources by staying active under teacher supervision through online learning platforms anywhere and anytime collaboratively (online discussions) or independently [50], [51]. In online learning, a teacher is a facilitator by providing eBooks, voice notes, and video tutorials as complementary materials for learning at home or independent study.…”
Section: )mentioning
confidence: 99%